2010
DOI: 10.1007/s11814-010-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the ash composition and melting temperature of waste incineration residue

Abstract: The correlation between the ash composition of various incinerated waste residues and their melting temperatures was examined by using their chemical composition parameters. There was a low correlation between the melting temperatures and the acidic oxide content in the ashes. However, the composition parameters derived from the basic oxides showed a good correlation with the ash melting temperature. The composition parameter, P 7 , which is defined as the ratio of basic oxides (CaO+MgO+K 2 O+Na 2 O) to acidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Thus, the combined Al 2 O 3 and SiO 2 content is often used as an empirical parameter to predict AFTs, especially the ash flow temperature. 33,34 We found that the total Al 2 O 3 + SiO 2 content in each ash sample was only 2.20, 2.49, 2.87, 1.50, and 0.76, respectively. However, the AFTs of ash sample 3, which had the most Al 2 O 3 + SiO 2 , were lower than those of ash sample 2.…”
Section: Results and Analysismentioning
confidence: 78%
“…Thus, the combined Al 2 O 3 and SiO 2 content is often used as an empirical parameter to predict AFTs, especially the ash flow temperature. 33,34 We found that the total Al 2 O 3 + SiO 2 content in each ash sample was only 2.20, 2.49, 2.87, 1.50, and 0.76, respectively. However, the AFTs of ash sample 3, which had the most Al 2 O 3 + SiO 2 , were lower than those of ash sample 2.…”
Section: Results and Analysismentioning
confidence: 78%
“…The development of such prediction models requires substantial analysis data on melting temperature. Another alternative is the fluidity analysis method, which is relatively simple and easily reproducible; this has been proposed in various studies [8,11,16,[19][20][21][22][23].…”
Section: Evaluation Of Slag Flowability By Fluidity Measurementmentioning
confidence: 99%
“…In order to successful slagging, the operation temperature must be higher than the temperature when the viscosity is 25 Pa•s. In addition, the suitable operation temperature can reduce oxygen and feedstock consumptions, extend refractory life and reduce costs, which is beneficial to yield product efficiently [9]. However, determination of the operational condition is not only closely related to the slagging viscosity but also to the rheology of slag, because the characters of rheology can be used to predict the change of viscosity.…”
Section: Introductionmentioning
confidence: 99%